MUSLIMS OF THE CAUCASUS IN THE RELIGIOUS POLICY OF THE DUKE M. S. VORONTSOV - Sergey S. Lazaryan; Yuri U. Klychnikov (Вестник Северо-Кавказского федерального университета)
In this article the authors reveal the essence of the religious policy of the Russian-Caucasian administration in the years of the governorship M. S. Vorontsov, which persecuted, first of all, the Imperial goals and be directed at the soonest involvement of the Caucasus in the system of Imperial life.